Translation as metaphor - Guldin, Rainer (Translation theories explored, 2016)
In today's ever-changing climate of disintegration and recombination, translation has become one of the essential metaphors, if not the metaphor, of our globalized world. Translation and Metaphor is an attempt to draw a comprehensive map of these new overlapping theoretical territories and the many cross-disciplinary movements they imply.